2023
DOI: 10.3389/fimmu.2023.1214677
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in multiple system atrophy

Abstract: Misfolding protein aggregation inside or outside cells is the major pathological hallmark of several neurodegenerative diseases. Among proteinopathies are neurodegenerative diseases with atypical Parkinsonism and an accumulation of insoluble fibrillary alpha-synuclein (synucleinopathies) or hyperphosphorylated tau protein fragments (tauopathies). As there are no therapies available to slow or halt the progression of these disea ses, targeting the inflammatory process is a promising approach. The inflammatory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 104 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Therefore, a more detailed investigation is necessary, including experimental groups categorized by both clinical criteria and brain regions. A more comprehensive review of the issue can be found elsewhere. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a more detailed investigation is necessary, including experimental groups categorized by both clinical criteria and brain regions. A more comprehensive review of the issue can be found elsewhere. …”
Section: Resultsmentioning
confidence: 99%
“…Chronic inflammation induces cancer, autoimmune disorders, metabolic disorders, and neurological diseases, such as AD, PD, and ALS. In the brain, inflammation induces the reactions of glial cells (astrocyte and microglial acti-vation) and an increase in the production of proinflammatory cytokines, such as IL-2 and IL-13 [40], by circulating immune cells, including monocytes, neutrophils, and lymphocytes. In addition, neurodegenerative diseases are characterized by the impairment of inflammatory events.…”
Section: Discussionmentioning
confidence: 99%
“…A more comprehensive review of the issue can be found elsewhere. [47][48][49][50][51] More on the Vimentin protein in view of caspase activity. During manual inspection of DEPs reported by DirectMS1 method, we noticed that most valuable information showing differential expression of Vimentin protein comes from peptides from the middle (104-236 amino acid positions) and last part (294-410) of the protein sequence (Supplementary Table 2).…”
Section: P06576 Proteinmentioning
confidence: 99%